Kajian Kemasan Tape Ketan sebagai Identitas Khas Kuningan Jawa Barat: Studi Kasus: Merek Harum Sari - Rukiah, Yayah (Magenta | Official Journal STMK Trisakti, 2018)
MEA (ASEAN Economic Community) entered into Indonesia in 2016. One of the industries that is the pillar of the populist economy is UMKM industry. This industry goes into culinary Enterprises. Culinary business that enter into the group of SMEs among them is Tape Ketan Business which is generally produced by home industry. This research method is a critical study on the circulation of design work in the form of packaging design and plastic content of glutinous tape product typical of Kuningan brand Harum Sari. Typical glutinous tape is packed in a unique way. Although actually not much different, the uniqueness is there because the tape is packed in a bucket and the content of plastic contained therein endanger health. But the black bucket will not be replaced and still be used because this is typical of typical sticky tape packaging of Kuningan Regency of West Java.